1996
DOI: 10.1016/s0092-8674(00)80132-4
|View full text |Cite
|
Sign up to set email alerts
|

Dorsoventral Patterning in Xenopus: Inhibition of Ventral Signals by Direct Binding of Chordin to BMP-4

Abstract: Chordin (Chd) is an abundant protein secreted by Spemann organizer tissue during gastrulation. Chd antagonizes signaling by mature bone morphogenetic proteins (BMPs) by blocking binding to their receptors. Recombinant Xenopus Chd binds to BMP-4 with high affinity (KD, 3 x 10(-10) M), binding specifically to BMPs but not to activin or TGF-beta1. Chd protein is able to dorsalize mesoderm and to neuralize ectoderm in Xenopus gastrula explants at 1 nM. We propose that the noncell-autonomous effects of Spemann's or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
602
1
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,026 publications
(624 citation statements)
references
References 47 publications
15
602
1
6
Order By: Relevance
“…These are similar to Von Willebrand factor type C repeats found in the secreted BMP antagonist Chordin (Chrd) and its homologue in Drosophila, Short gastrulation (Sog; Francois et al, 1994;Sasai et al, 1994Sasai et al, , 1995. CHRD inhibits BMP-2, BMP-4, and BMP4/7 heterodimers by direct binding and inhibition of BMP receptor activation (Piccolo et al, 1996). The Von Willebrand factor type C repeats in CHRD modulate this binding, and individual repeats can bind to BMPs with reasonable affinity (Larrain et al, 2000).…”
Section: Introductionmentioning
confidence: 72%
“…These are similar to Von Willebrand factor type C repeats found in the secreted BMP antagonist Chordin (Chrd) and its homologue in Drosophila, Short gastrulation (Sog; Francois et al, 1994;Sasai et al, 1994Sasai et al, , 1995. CHRD inhibits BMP-2, BMP-4, and BMP4/7 heterodimers by direct binding and inhibition of BMP receptor activation (Piccolo et al, 1996). The Von Willebrand factor type C repeats in CHRD modulate this binding, and individual repeats can bind to BMPs with reasonable affinity (Larrain et al, 2000).…”
Section: Introductionmentioning
confidence: 72%
“…Isolation of sufficient material from specific anatomic regions was facilitated by the large size of Xenopus embryos, whereas the dorsalizing manipulations were only possible because of the accessibility of the early embryo and the large background knowledge of how such manipulations are carried out (Blumberg et al, 1991). Further biochemical studies that showed that both noggin and chordin proteins could bind BMP4 directly to inhibit its activity (Zimmerman et al, 1996;Piccolo et al, 1996).…”
Section: Morphogens In Vivo Part Ii: Fgfs and Bmpsmentioning
confidence: 99%
“…Next, we investigated effects of BMP-4 protein and its antagonist, Chordin, on the X. laevis intestinal remodeling by using the organ culture system established previously (Ishizuya-Oka and Shimozawa, 1991). Although there are more than seven known antagonists of BMP-4 in vertebrates (Balemans and Hul, 2002), we used Chordin to inhibit BMP-4 activity, because it binds BMP-4 with a high affinity (Piccolo et al, 1996). In addition, we previously identified a Xenopus homolog of Drosophila Tolloid closely related to BMP-1 (Tolloid/BMP-1), which is known to degrade Chordin (Piccolo et al 1997;Wardle et al, 1999;Blitz et al, 2000;Balemans and Hul, 2002), as a TH response gene in the X. laevis intestine (Shimizu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%